2008
DOI: 10.3152/095820208x240208
|View full text |Cite
|
Sign up to set email alerts
|

Research evaluation per discipline: a peer-review method and its outcomes

Abstract: Context & GoalsResearch evaluations are conducted with different goals and at different governance levels. Goals set by the university's research management (e.g. internal quality assessment, definition of spearhead research groups, evaluation of the PhD support and training processes, ex-ante and ex-post project evaluations) may be very different from those set by national authorities (e.g. foundation or justification for university funding, mapping of the global research potential, rationalizing the higher e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The focus of these evaluations is research, in particular research quality. Expert panel review is considered the standard for determining research quality of individuals and groups (Nedeva et al, 1996;Rons et al, 2008;Butler & McAllister, 2011;Lawrenz et al, 2012), but also, for instance, for research proposals submitted to research funding organizations (Li & Agha, 2015). In 2007, the University of Antwerp, Belgium, decided to introduce evaluative site visits by expert panels, during which the panel meets the spokesperson of each research group and other relevant stakeholders, and panel members are given the opportunity to ask additional questions or request clarification of specific points described in the self-evaluation report they received in advance.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of these evaluations is research, in particular research quality. Expert panel review is considered the standard for determining research quality of individuals and groups (Nedeva et al, 1996;Rons et al, 2008;Butler & McAllister, 2011;Lawrenz et al, 2012), but also, for instance, for research proposals submitted to research funding organizations (Li & Agha, 2015). In 2007, the University of Antwerp, Belgium, decided to introduce evaluative site visits by expert panels, during which the panel meets the spokesperson of each research group and other relevant stakeholders, and panel members are given the opportunity to ask additional questions or request clarification of specific points described in the self-evaluation report they received in advance.…”
Section: Introductionmentioning
confidence: 99%
“…The Government Accountability Office (GAO) found that expert panel review and site visits were frequently used in evaluating federal program performance for all federal programs (GAO, ). In terms of validity, expert panel review is viewed as the gold standard for ascertaining research quality and other assessment methods are often compared to it (Butler & McAllister, ; Rons, DeBruyn & Cornelis, ). Generally, this type of site visit is conducted by a team of experts who provide a connoisseurship approach to evaluation (Eisner, ) and follow procedures outlined in Lawrenz, Thao, and Johnson ().…”
Section: Case Three: Assessing Research Center Qualitymentioning
confidence: 99%
“…Otros autores plantean modelos de evaluación del desempeño para las actividades científicas en ámbitos específicos como las instituciones públicas (Coccia, 2005), la importancia de que ese proceso se realice con las particularidades de cada disciplina (Benneworth & Jongbloed, 2010;Broadhead & Howard, 1998;Lewison et al, 2007;Rons et al, 2008).…”
Section: Revisar O Analizar Los Parámetros De Financiación O Recompensaunclassified